2017
DOI: 10.1038/mp.2016.259
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies two novel susceptibility loci and trans population polygenicity associated with bipolar disorder

Abstract: Genome-wide association studies (GWASs) have identified several susceptibility loci for bipolar disorder (BD) and shown that the genetic architecture of BD can be explained by polygenicity, with numerous variants contributing to BD. In the present GWAS (Phase I/II), which included 2964 BD and 61 887 control subjects from the Japanese population, we detected a novel susceptibility locus at 11q12.2 (rs28456, P=6.4 × 10−9), a region known to contain regulatory genes for plasma lipid levels (FADS1/2/3). A subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
179
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(190 citation statements)
references
References 32 publications
(50 reference statements)
11
179
0
Order By: Relevance
“…In addition to our Chinese sample, we also collected the statistical data (OR and p value) of rs1064395 from two independent Japanese samples (Japan 01: 1,545 cases and 7,408 controls; Japan 02: 1,419 cases and 54,479 controls) [20] and six European datasets (MooDS GWAS, PGC1 GWAS, Iceland, France, Bosnia and Herzegovina/Serbia, and Romania) from previously published studies [13, 17, 18, 31]. The PGC1 GWAS statistical results were obtained from the Psychiatric Genomics Consortium public website (https://www.med.unc.edu/pgc).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to our Chinese sample, we also collected the statistical data (OR and p value) of rs1064395 from two independent Japanese samples (Japan 01: 1,545 cases and 7,408 controls; Japan 02: 1,419 cases and 54,479 controls) [20] and six European datasets (MooDS GWAS, PGC1 GWAS, Iceland, France, Bosnia and Herzegovina/Serbia, and Romania) from previously published studies [13, 17, 18, 31]. The PGC1 GWAS statistical results were obtained from the Psychiatric Genomics Consortium public website (https://www.med.unc.edu/pgc).…”
Section: Methodsmentioning
confidence: 99%
“…28 These conform to the well-known calcium dysregulation hypothesis of bipolar disorder 55 and also the mitochondrial dysfunction hypothesis. 57,58 Because fatty acid composition of CL in the brain is unique in particular, 59 further detailed F I G U R E 8 CRC of mitochondria obtained from the brains of cKO and control mice. Large-scale, genome-wide association studies of the disease, however, highlighted FADS1,2 genes involved in the polyunsaturated fatty acids metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting and novel susceptibility gene is Fatty acid desaturase 1/2/3 ( FADS1/2/3 ), which was detected by our research group (advanced COSMO) . It is also noteworthy that this study used a non‐European sample and was the largest in the East Asian population.…”
Section: Summary Of Gwas Findingsmentioning
confidence: 91%
“…Therefore, it is difficult to pinpoint the ‘genuine’ susceptibility genes solely on the basis of these results. Trans‐ethnic replication analysis is reasonable for this purpose and in this aspect, it is stressed that the SNP near FADS genes were associated with BD in the updated PGC data, which indicated that the trans‐population effect exists in the FADS region as a risk for BD between European and Asian populations.…”
Section: Summary Of Gwas Findingsmentioning
confidence: 94%
See 1 more Smart Citation